Antioxidant and Laxative Effects of Methanol Extracts of Green Pine Cones (Pinus densiflora) in Sprague-Dawley Rats with Loperamide-Induced Constipation - Hee-Jin Song; Ayun Seol; Jumin Park; Ji-Eun Kim; Tae-Ryeol Kim; Ki-Ho Park; Eun-Seo Park; Su-Jeong Lim; Su-Ha Wang; Ji-Eun Sung; Youngwoo Choi; Heeseob Lee; et al. (Antioxidants)
Oxidative stress is the key cause of the etiopathogenesis of several diseases associated with constipation. This study examined whether the green pine cone can improve the symptoms of constipation based on the antioxidant activities. The changes in the key parameters for the antioxidant activity and laxative effects were examined in the loperamide (Lop)-induced constipation of Sprague-Dawley (SD) rats after being treated with the methanol extracts of green pine cone (MPC, unripe fruits of Pinus densiflora). MPC contained several bioactive compounds, including diterpenoid compounds such as dehydroabietic acid, taxodone, and ferruginol. In addition, it exhibited high scavenging activity against 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radicals. These effects of MPC successfully reflected the improvement in nicotinamide adenine dinucleotide phosphate oxidase (NADP) H oxidase transcription, superoxide dismutase (SOD) levels, and nuclear factor erythroid 2-related factor 2 (Nrf2) phosphorylation levels in the mid colon of Lop+MPC-treated SD rats. Furthermore, significant improvements in the stool parameters, gastrointestinal (GI) transit, intestine length, and histopathological structure of the mid colon were detected in the Lop-induced constipation rats after MPC treatment. The other parameters, including the regulators for the adherens junction (AJ) and tight junction (TJ), and GI hormone secretion for laxative effects, were improved significantly in Lop+MPC-treated SD rats. These effects were also verified in Lop+MPC-treated primary rat intestine smooth muscle cells (pRISMCs) through analyses for antioxidant defense mechanisms. Overall, the finding of this study offers novel scientific evidence that MPC could be considered as a significant laxative for chronic constipation based on its antioxidant activity.